Fatty acid composition of serum cholesterol esters and triacylglycerols in a South-Western Cape population and relation to diet - Botha, Elizabeth Ann (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc (Dietetics)) -- University of Stellenbosch, 1987.